Brain Abscess Caused by Nocardia farcinica and Diagnosed by Metagenomic Next-Generation Sequencing: A Case Report - Yang, Jianhua; Xie, Shuhua; Li, Junda; Xia, Han; Liu, Xianghong (Frontiers in Medicine, 2022)
Background Brain abscesses caused by Nocardia farcinica are rare and difficult to diagnose. Conventional methods for diagnosing Nocardia species include blood culture, microscopy, and tissue slice, but the performance is not satisfied. We report a case of brain abscess due to N. farcinica diagnosed by metagenomic next-generation sequencing (mNGS). Case Presentation We report a case of a 58-year-old man with brain abscess caused by N. farcinica. The patient had a history of pemphigus and required long-term methylprednisolone administration. No pathogen was detected in blood culture, cerebrospinal fluid (CSF) culture, and fast-acid staining. mNGS identified N. farcinica in the CSF. The symptoms and signs of the patient were significantly improved after changing the antibiotics accordingly to sensitive antibiotics. Conclusion Metagenomic next-generation sequencing (mNGS) is helpful for early diagnosis and subsequent treatment of Nocardia-associated meningitis and encephalitis, avoiding brain surgery. Early and accurate diagnosis and prompt antibiotic treatment reduced its mortality.